Outcome of the “Manchester Groin Repair” (Laparoscopic Totally Extraperitoneal Approach With Fibrin Sealant Mesh Fixation) in 434 Consecutive Inguinal Hernia Repairs - Pilkington, J. James; Obeidallah, M. Rami; Zahid, M. Saad; Stathakis, Panagiotis; Siriwardena, Ajith K.; Jamdar, Saurabh; Sheen, Aali J. (Frontiers in Surgery, 2018)
Introduction: This study looks at the outcome of 352 patients that underwent the ‘Manchester groin repair’ in the period from 2007 to 2016. The effect of laterality on chronic groin pain and the reduction of pain scores post-surgery are evaluated as well as the rate of hernia recurrence for the inguinal hernia repairs. Methods: The ‘Manchester groin repair’ is a modification of a laparoscopic totally extra-peritoneal approach with fibrin sealant mesh fixation. Data were collected prospectively. In addition to demographic data and the European Hernia Society classification grading of each hernia, pain scores were assessed prior to surgery and at 4-6 weeks post-operatively using a ten-point visual analogue pain scale. Data were collected on a bespoke database and differences between time-points analysed by non-parametric Wilcoxon signed rank tests with Kruskal-Wallis rank sum test for three-group comparisons. Significance was at the P<0.05 level. The study was undertaken as an institutional audit. Results: 352 patients underwent TEP repair as per the ‘Manchester Groin Repair’ modification during the period of interest with a median follow-up period of 109.5 (IQR 57.0 – 318.5) weeks. Of these 274 (77.8%) were for the repair of true hernias and 78 (22.2%) were for inguinal disruptions. All inguinal hernia repairs patients were evaluated (254m, 20f); median [interquartile range] age 50 (39-65) years. There were 75 right inguinal hernias (27.4%), 39 Left inguinal hernias (14.2%) & 160 bilateral inguinal hernias (58.4%), giving a total of 434 hernia repairs. During follow-up there were 6 recurrences (1.4%). Of the 274 patients evaluated, 145 (52.9%) had both pre and post-operative pain scores available. Median pre-operative pain score was 5 [IQR 4 – 7]. Median post-operative pain score was 1 [IQR 1-2]. This difference was significant (P<0.001). Pre-operative pain scores were higher for those with a bilateral hernia (median 6 vs 5 and 4 respectively; P=0.005), but there was no difference in post-operative scores (P=0.347). One patient (0.3%) presented with chronic groin pain (pain after three months). Conclusion: This study demonstrates that the ‘Manchester groin repair’ provides an excellent repair with a low rate of recurrence and low incidence of chronic pain.